Chitosan combined with technical cashew nut shell liquid improves in vitro ruminal parameters and gas production kinetics - de Queiroz Vieira, Elis Regina; e Buschinelli, Rafael Henrique de Tonissi; Diaz, Tatiana Garcia; Osmari, Milene Puntel; de Oliveira Seno, Leonardo; Ítavo, Luís Carlos Vinhas; Gandra, Jefferson Rodrigues; Anschau, Douglas Gabriel; de Oliveira, Raquel Tenório; da Silva, Nayara Gonçalves; Jacaúna, Amanna Gonzaga [UNESP] (Revista Brasileira de Zootecnia, 2022)
The objective was to evaluate the inclusion of chitosan (CHI) and technical cashew nut shell liquid (CNSLt) as natural feed additives in cattle diets on nutrient digestibility, ruminal fermentation, and in vitro gas production kinetics. We conducted a completely randomized design with 5×4 factorial arrangement, with 20, 35, 50, 65, and 100% Tifton 85 hay and four additives, monensin (200 mg/kg DM), CNSLt (500 mg/kg DM), CHI (500 mg/kg DM), and CNSLt+CHI (500 mg/kg DM/each). Dry matter (DM) and organic matter (OM) digestibility showed a linear reduction according to forage levels. The highest DM digestibility was observed with CHI on cattle diets. Inclusion of CHI increased DM digestibility. The highest in vitro organic matter and crude protein (CP) digestibilities were observed for CNSLt+CHI. The in vitro dry matter digestibility increased linearly with concentrate in the diet. There was interaction of forage:concentrate ratio and the additives for neutral detergent fiber, acid detergent fiber and hemicellulose digestibility. Chitosan, CNSLt, and CNSLt+CHI promoted the lowest acetate:propionate ratio compared with monensin. Total gas production showed interaction of the forage:concentrate ratio and additives. Lag time was lowest with CNSLt+CHI. Chitosan and CNSLt can be considered alternative fermentation modulators to ionophores by improving nutrient digestibility and increasing ruminal propionate concentrations.
Keywords: Gas production; Natural feed additives; Rumen fermentation; Short-chain fatty acids